Selective CO oxidation over monolithic Au/Al2O3 promoted by metal oxides - Özdemir, Seval. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
The objective of this study was to investigate the preparation methods of cordierite monolithic Au/MgO/Al2O3 catalysts for selective carbon monoxide oxidation in a hydrogen rich environment. In this comparative study, the walls of the monolithic structures were firstly coated with alumina by colloidal coating method in order to enlarge the surface area of the catalyst. The loading of the metal oxide promoter (MgO) to the monolithic structure was applied by impregnation method. Gold was loaded to the MgO/Al2O3/cordierite monolith catalysts using five different methods namely, wet impregnation, co-precipitation, dry impregnation, deposition-precipitation and homogeneous deposition precipitation. Deposition precipitation technique was applied both at 70oC and room temperature, and homogeneous deposition precipitation method was applied by using two different precipitating agents which are acetamide and urea. The catalysts were then reduced in H2 with a flow rate of 50 cm3min-1 for 2 hours and tested for selective carbon monoxide oxidation in a hydrogen rich stream. The comparison of the gold loading methods was studied at 110oC and the MgO and Au content of the catalysts were selected as 1.25 wt% and 1 wt% respectively. Catalysts with 0.5 wt% and 0.16 wt% Au content were also studied in order to determine the Au loading effect. The effects of Au and MgO loading, W/F ratio and O2 content were investigated in the temperature range of 50-150oC under a total flow of 100.6 ml/min. Finally, the effect of temperature ascent and descent was investigated. The highest CO conversion (77.30%) was achieved via homogeneous deposition precipitation method using urea as the precipitating agent at 90oC with the catalyst compositions of 1 wt% Au/1.25 wt% MgO/Al2O3 and with the feed compositions of 0.99% CO, 1.59% O2, 59.64% H2 and balance He.
Keywords: Fuel cells.; Carbon monoxide.; Oxidation.; Catalysts.